Long term renal outcome after hypertensive disease during pregnancy: a nationwide population-based study - Kwang Hyun Lee; Ji Hye Bae; Jeesun Lee; Young Mi Jung; Chan-Wook Park; Joong Shin Park; Jong Kwan Jun; Geum Joon Cho; Seung Mi Lee (Korean Society of Obstetrics and Gynecology, 2023)
Objective Hypertensive disease during pregnancy increases the risk of maternal morbidity and mortality and leads to the development of multi-organ dysfunction, including kidney dysfunction. Complicated pregnancies require careful postpartum management to prevent sequelae. It is believed that kidney injury can consistently occur even after delivery; therefore, defining the chronicity and endpoint is essential for establishing diagnostic criteria. However, data on the prevalence of persistent renal complications following hypertensive disease during pregnancy are limited. In this study, we evaluated the risk of developing renal disorders in patients with a history of hypertensive disease during pregnancy. Methods Participants who gave birth between 2009 and 2010 were followed up for 8 years after delivery. The risk of renal disorder development after delivery was determined according to a history of hypertensive disease during pregnancy. Different factors that could affect the course of pregnancy, including age, primiparity, multiple pregnancy, preexisting hypertension, pregestational diabetes, hypertensive disease during pregnancy, gestational diabetes, postpartum hemorrhage, and cesarean section, were adjusted for using the Cox hazard model. Results Women with hypertension during pregnancy had a higher risk of developing renal disorders after delivery (0.23% vs. 1.38%; P<0.0001). This increased risk remained significant even after adjusting for covariates (adjusted hazard ratio, 3.861; 95% confidence interval [CI], 3.400-4.385] and 4.209 [95% CI, 3.643-4.864]; respectively). Conclusion Hypertension during pregnancy can contribute to the development of renal disorders, even after delivery.